From Knowledge Carrier to Disciplinary Knowledge Mediator: The profile of the Professor of Library-archival Science and Information Science - Jaramillo, Orlanda (2018)
The text presents an overview of the profile of the teacher of library-archival and information science, which depends both on the characteristics of the curriculum (pedagogical project, educational model) and the characteristics of the teacher. The results are exposed in two sections: one related to the documentary search, which are presented in idea maps, grouped into four areas (theoretical foundation, organization and representation of information and knowledge, management and ICT); the other corresponds to the characteristics of the professors attached to the Colombian universities that provide training in the area.